Intervention for congenital and structural heart disease: Beyond the cradle - Weich, Hellmuth; Brown, Stephen (SA Heart Journal, 2017)
During the last four decades we have seen an exponential growth in interventions (both medical and invasive) to diagnose and treat adult cardiac disorders. Coronary stents are in their fourth generation and the developments in cardiac pacing and electrophysiology has shown the same rapid growth. Large numbers of patients at risk who require these treatment modalities have driven these developments and the interventions have made a difference to the lives of hundreds of thousands of patients across the globe.